Community Empowerment Based on Local Potential: A Case Study of Spice Management in Cikawung Village, Garut - Fariq Mahesa; Syasya Nur'aini; Mirna Nur Alia; Elly Malihah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Community empowerment based on local potential plays an important role in improving village welfare. The village of Cikawung in Garut has a variety of spice commodities such as nutmeg, cloves, ginger, palm sugar, and cardamom, which are local economic potentials. This study aims to identify the economic potential of Cikawung's spice community, reveal the factors hindering empowerment in the spice sector (particularly road access, facilities, and human resources), and analyze the role of participatory empowerment models in increasing community capacity. The research method was a qualitative case study with a participatory approach; data was obtained through field observations, in-depth interviews with community leaders (Mr. Yadi and Mr. Rahyat), and documentation. The main results show that the potential of local spices in Cikawung has not been optimally utilized. Significant obstacles include inadequate road infrastructure, limited production facilities, and low access to knowledge and motivation among local human resources. Meanwhile, the application of a participatory model involving residents from planning to product marketing appears to be able to increase a sense of ownership and business sustainability. It is concluded that to maximize the potential of Cikawung spices, inclusive empowerment programs, continuous training, and strengthening of marketing networks are needed so that spice management becomes a source of sustainable income.